Interest rates, saving and growth in Guyana - Kendall, Patrick ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1998)
Reviews the relationship between the interest rate on savings depoisits, gross demestic savings and real GDP growth during 1965 to 1995. Seeks to determine whether a more liberal financial policy stance would have resulted in increased savings and higher real GDP growth.